2023
DOI: 10.4103/ijmy.ijmy_217_22
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcome of Individual Regimens Containing Bedaquiline and Delamanid in Drug-Resistant Tuberculosis: A Systematic Review

Abstract: Background: Drug-resistant tuberculosis (DR-TB) is a public health concern that is difficult to treat, requiring long and complex treatment with highly effective drugs. Bedaquiline and/or delamanid have already shown promising outcomes in patients with DR-TB, increasing the rate of culture conversion and lowering TB-related mortality. Methods: We comprehensively searched and evaluated the effectiveness of individual regimens containing bedaquiline and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Overall, the treatment success rate was 69.7% among the pre-XDR TB patients [ 1 ]. Our previous study reported that in DR-TB patients who received regimens containing bedaquiline and delamanid, favorable outcomes (treatment success and treatment completion) at the end of treatment ranged from 67.5% to 91.4% [ 9 ]. Furthermore, a study in South Korea by Kang et al [ 10 ] and Hwang et al [ 11 ], demonstrated that regimens containing bedaquiline and/or delamanid showed highly favorable outcomes without any significant differences in adverse events in MDR, pre-XDR, and XDR-TB patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the treatment success rate was 69.7% among the pre-XDR TB patients [ 1 ]. Our previous study reported that in DR-TB patients who received regimens containing bedaquiline and delamanid, favorable outcomes (treatment success and treatment completion) at the end of treatment ranged from 67.5% to 91.4% [ 9 ]. Furthermore, a study in South Korea by Kang et al [ 10 ] and Hwang et al [ 11 ], demonstrated that regimens containing bedaquiline and/or delamanid showed highly favorable outcomes without any significant differences in adverse events in MDR, pre-XDR, and XDR-TB patients.…”
mentioning
confidence: 99%
“…It could represent a new treatment option to improve compliance in patients with fluoroquinolone-sensitive MDR-TB. However, concomitant use of bedaquiline and delamanid is rare in clinical settings due to their potential adverse events, such as corrected QT (QTc) prolongation [ 9 ]. Therefore, measurement of QTc interval should be closely supervised during these treatments.…”
mentioning
confidence: 99%